The influence of electronic module of marriage age maturity towards the self-efficacy of adolescent cadres in conducting education in Youth Information and Counseling Center (PIK-R), Bantul Regency - Pratiwi, Ufairoh Salma; Wahyuningsih, Wahyuningsih; Yugistyowati, Anafrin (Alma Ata University Press, 2024)
Background: Insufficient understanding of marriage-age maturity education related to self-efficacy among adolescent cadres contributes to early marriage and pregnancy at a young age, consequently elevating the risk of maternal mortality. Adolescent cadres play a crucial role as both peer groups and agents of change. Addressing this issue can be facilitated through the use of electronic modules, which have demonstrated effectiveness.Objectives: This study aims to determine the influence of electronic module of marriage age maturity towards the self-efficacy of adolescent cadres in conducting education in Youth Information and Counseling Center (PIK-R), Bantul Regency.Methods: This research employed a non-equivalent quasi-experimental design featuring pre-test and post-test assessments with a control group setup. The sample was selected through total sampling, comprising 50 respondents divided into two groups: 24 in the intervention group at Ngireng-ngireng Village (PIK-R Fresh) and 26 in the control group at Padokan Lor Village (PIK-R Pelangi). This research was conducted from February to March 2023. The instruments used in the study, including the electronic module of marriage age maturity and a self-efficacy questionnaire for adolescent cadres. The analysis used in this research was the paired sample t-test. Results: The paired sample t-test statistical analysis yielded a significant value of p-value 0.000 (p<0.05). This indicates that there is an influence on self-efficacy in the intervention group and the control group after being provided with education about marriage-age maturity using electronic modules and PowerPoint slides.Conclusions: The electronic modules of marriage-age maturity education have an impact on the self-efficacy of adolescent cadres involved in education in PIK-R, Bantul Regency. Consequently, it's advisable for adolescent cadres to integrate these electronic modules into their daily routines to boost their self-efficacy and educate their peers more effectively.